Social innovation - (Accompanying) instrument for addressing societal challenges? - Karl Matthias Weber; Susanne Giesecke; Attila Havas; Doris Schartinger; Andreas Albiez; Sophia Horak; Knut Blind; Miriam Bodenheimer; Stephanie Daimer; Liu Shi; Maria Stadler; David Schmitz (Expertenkommission Forschung und Innovation (EFI), 2024)
The importance of social innovation for overcoming societal challenges is now widely recognised. In addition to their contribution to the transformation of socio-technical systems, they are also assigned an important role in flanking disruptive technological developments and coping with crisis situations such as the COVID-19 pandemic. At the same time, the theoretical understanding of social innovations is very heterogeneous, which is detrimental to both the development of measurement concepts and indicators and the well-founded derivation of innovation policy measures. Building on recent research, a conceptual process model of social innovation is developed and subsequently used to analyse four case studies (energy communities, autonomous driving, corona warning app, social housing in Vienna). In addition, the report deals with rationales for justifying state interventions in social innovation, as well as with the use of new policy instruments to support social innovations in four pioneering countries. It also assesses the current state of research on the measurement and indicators of social innovation. It concludes with implications for the research and innovation policy debate in Germany.
Keywords: 330